China Carbon Neutralization Research Status and Research Frontier Tracking - Shi, Xiaoliang; Zhang, Jiayi; Lu, Shuaiyu; Wang, Tielong; Zhang, Xinyue (Frontiers in Environmental Science, 2022)
In the context of global joint response to climate change, carbon neutralization has become one of the main measures for governments, enterprises and even individuals around the world to deal with global warming.This paper explores the current research status and frontier trends in the field of carbon neutralization, which can not only provide theoretical reference for the follow-up research of carbon neutralization, but also provides useful ideas for the policy-making of carbon neutralization.The study is built on the China National Knowledge Infrastructure (CNKI) Core Journals Database, the Chinese Social Sciences Citation Index (CSSCI) database and the Chinese Science Citation Database (CSCD) database as the literature retrieval database platform. Using CiteSpace optical measurement software, 370 pieces of literature in the field of carbon neutrality research in China were systematically analyzed to track the situation and impact of research by various research institutions and prominent authors in China in this field and to analyze the research hotspots in this field, which is of great significance for the follow-up research of carbon neutrality. The research results show that: 1) The number of publications in China's carbon-neutral field has increased significantly with the change of years and has strong development potential. 2) Journals with many articles are more concentrated and are generally published in three journals: Natural Gas Industry, Proceedings of the CSEE and Chinese Science Bulletin. 3) In terms of major research institutions, the Institute of National Conditions of Tsinghua University, the School of Public Administration of Tsinghua University, the School of Grammar of Beijing University of Technology, and the Economic Development Research Center of the State Forestry and Grassland Administration have published more papers and muscular scientific research strength in the field of carbon neutrality. 4) In terms of the principal authors, four typical research teams have been set up: low-carbon economy, low-carbon cycle, carbon trading, sewage carbon neutrality, environmental science and resource utilization, and the authors of each research team cooperate closely. 5) In the future, the research hotspots in China's carbon-neutral field are still the themes of carbon emission reduction, green and low carbon, new energy, etc.,